Early changes in the visual system connected with brain's aneurysm rupture - Obuchowska, Iwona; Kochanowicz, Jan; Mariak, Zofia; Mariak, Zenon (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: To evaluate frequency and type of early changes in the visual system connected with brain’s aneurysm rupture. Material and methods: 45 patient, 34 women and 11 men, with subarachnoid hemorrhage (SAH) after brain’s aneurysm rupture were enclosed in this study. To identify aneurysm, cerebral angiography as well as CT or MR angiography were applied. Conventional ophthalmologic examination and Doppler sonography of the retrobulbar vessels were performed in all patients before and two or three days after neurosurgical procedure. Results: The mean age of patients with SAH was 47.6 years. Female/ male ratio was 3: 1. The most common site of aneurysm was at the origin of the middle cerebral artery (37.8%), or anterior communicating artery (28.9%). In 73.3% of patients aneurysm were asymptomatic at diagnosis. The rest patients had some prodromal symptoms, including ocular signs (wide pupil, opressive feeling on the globe, diplopia or visual disturbances), in 15% of one’s. Sudden headache (80%), was the most characteristic symptom of brain aneurysm rupture. In 20% the first sign of SAH was loss of consciousness. Papilledema and intraocular hemorrhages occurred in 25 patients (55.6%), and wide pupil in 4 person (8.9%). Among patients with hemorrhagic changes 3 person (6.7%), had Terson syndrome. Conclusions: Female gender seem to increase the risk for intracranial aneurysm formation. Among symptoms, which are presenting manifestations of brain’s aneurysm, ocular signs play the important role. Brain’s aneurysm rupture is always connected with severe neurological symptoms. More than half of patients with SAH after intracranial aneurysm rupture have fundal hemorrhagic changes in fundus